2019
DOI: 10.1038/s41598-019-51246-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased interactions and engulfment of dendrites by microglia precede Purkinje cell degeneration in a mouse model of Niemann Pick Type-C

Abstract: Niemann Pick Type-C disease (NPC) is an inherited lysosomal storage disease (LSD) caused by pathogenic variants in the Npc1 or Npc2 genes that lead to the accumulation of cholesterol and lipids in lysosomes. NPC1 deficiency causes neurodegeneration, dementia and early death. Cerebellar Purkinje cells (PCs) are particularly hypersensitive to NPC1 deficiency and degenerate earlier than other neurons in the brain. Activation of microglia is an important contributor to PCs degeneration in NPC. However, the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 56 publications
2
39
0
Order By: Relevance
“…Previous work in our laboratory showed significant changes in microglia number, morphology and phagosome content in the cerebellum of Npc1 nmf164 mice at post-weaning age and before PC degeneration (Kavetsky et al, 2019). Interestingly, the migration, proliferation and differentiation of cerebellar microglia occur postnatally along with the development and differentiation of cerebellar neurons.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous work in our laboratory showed significant changes in microglia number, morphology and phagosome content in the cerebellum of Npc1 nmf164 mice at post-weaning age and before PC degeneration (Kavetsky et al, 2019). Interestingly, the migration, proliferation and differentiation of cerebellar microglia occur postnatally along with the development and differentiation of cerebellar neurons.…”
Section: Introductionmentioning
confidence: 72%
“…Interestingly, recent studies have shown that genetic inactivation of reactive microglia in Npc1 −/− mice reduces neurological impairment and increases their life span (Cougnoux et al, 2018). We recently found that engulfment and phagocytosis of dendrites by activated microglia occur early and precede PC loss in NPC (Kavetsky et al, 2019), demonstrating that activated microglia contribute to PC degeneration in NPC.…”
Section: Introductionmentioning
confidence: 86%
“…Another condition, a mouse model of Niemann-Pick type C, where neurodegeneration and inflammation are found, revealed the presence of the DM. Indeed, Kavetsky et al (2019) investigated NPC nmf164 mice given for 5 weeks either a Western diet or a regular diet. Niemann-Pick type C is a genetic condition with mutations in the NPC genes (Npc1/2), which most notably lead to dysfunctional lysosomes (Wheeler and Sillence, 2019).…”
Section: Neurodegenerative Diseases and Neuroinflammationmentioning
confidence: 99%
“…Moreover, HS fragments enhance integrin-based focal adhesions formation and activation in normal mouse astrocytes or in human neuronal progenitors, resulting in cell polarization and migration defects [43]. In the Npc1 -/mice, the mouse model of Niemann Pick type C 1 (NPC1), microglia contribute to the degeneration of Purkinje cells by engulfing and destroying their dendrites [44]. The same study also reported that microglia accumulated phagosomes and autofluorescent material that coincided with the degeneration of dendrites and Purkinje cells.…”
Section: Main Aspects Of Central Nervous System (Cns) Pathology In Nementioning
confidence: 99%